Comparison of remineralizing effect of organic and inorganic fluoride by evaluation of microhardness and quantitative analysis of calcium and phosphorus ratio on enamel surface: an in-vitro study - Karthik Prasad, Lokam; MD, Khwaja Moinuddin; X, Nagamaheshwari; P, Uday Kumar; K, Shekar; Kaushik, Mamta (International Journal of Dental Materials, 2020)
BackgroundEnamel is a highly mineralized tissue of the body which is composed of 96% inorganic salts and 4% organic matter. Enamel is permeable to water and ions, particularly cations and low molecular weight substances. The enamel continues to mature even after eruption with mineral replacing protein. Recently, the interest on the development of calcium phosphate-based remineralization technology has been increased that led to the development of various remineralizing agents like Fluoride, CPP-ACP (Tooth Mouse plus), Bioglass (Novamin), Ozone, Xylitol, Sensistat etc.Aim Aim of the present in vitro study was to evaluate and compare the remineralizing effect of Organic fluoride (AmF) and inorganic fluoride (NaF) by evaluating Vickers microhardness and quantitative analysis of Calcium and Phosphorus ratio on enamel surface using Scanning Electron Microscope-Energy Dispersive X-ray analysis.Materials and methodsSixteen maxillary central incisors were decoronated at the cementoenamel junction and mounted in cylindrical moulds filled with self-cure acrylic resin. Artificial demineralized lesions were created on the enamel surface by suspending them in 0.1 M Citric acid buffer at pH of 3.2 for 72 hrs. The samples were then randomly divided into two groups and labelled, Group A – remineralized with NaF for 3 minutes twice daily for one week and Group B - remineralized with AmF for 3 minutes twice daily for one week. Microhardness and SEM-EDX analysis were done before demineralization, after demineralization and after remineralization.ResultsData were analyzed by comparing the mean values between the groups using independent sample t-test. The intra-group analysis was done using repeated-measures ANOVA with posthoc Bonferroni test, and a p-value of